A review of the main histopathological findings in the Coronavirus Disease 2019 (COVID-19) (2020)
Coronavirus disease 2019 (COVID-19), caused by the SARS-CoV-2 virus, has been declared by the WHO as an emerging public health problem of global importance and classified as a pandemic. SARS-CoV-2 infection can result in diverse, multi-organ pathology, the most significant being in the lungs (diffuse alveolar damage in its different phases, microthrombi, bronchopneumonia, necrotizing bronchiolitis, viral pneumonia), heart (lymphocytic myocarditis), kidney (acute tubular injury), central nervous system (microthrombi, ischemic necrosis, acute hemorrhagic infarction, congestion, and vascular edema), lymph nodes (hemophagocytosis and histiocytosis), bone marrow (hemophagocytosis) and vasculature (deep vein thrombosis). An understanding of the spectrum and frequency of histologic findings in COVID-19 disease is essential for gaining a better understanding of disease pathophysiology and its ongoing impact on public health. To this end, we conducted a systematic meta-analysis of histopathologic observations to date and review the reported findings.